(untitled) (Eureka Journal of Civil, Architecture and Urban Studies, 2025)
The possibilities of energy saving and creating an optimal microclimate in public buildings through the implementation of energy-efficient external shading systems have been studied. The use of inorganic porous basalt material is recommended as a material for external shading. The data presented in the article confirm the expediency of using basalt material when combining different functional solutions (insulation, sun protection) in the development of modern external shading projects for civil buildings.